The effect of upper respiratory tract illness on exercise performance - Viljoen, Deon Andre (MRC/UCT RU for Exercise and Sport Medicine, 2018)
Two studies were undertaken to investigate the relationship between upper respiratory tract infection (URTI) and exercise performance. The first study documented the incidence of URTI in an athletic population and the second study determined the effect of URTI on exercise performance during the recovery period. Endurance runners (n=29) were used for these studies and the athletes were monitored for 45 months. During this time the subjects ran an average of 40 kilometers/week. In the first study, 22 reports of symptoms (n=22) of URTI occurred during the 45-month period. Of these, 10 subjects (n=10) were ill for less than 3 days. All 10 subjects reported their symptoms directly following an endurance event. The other 12 subjects (n=12) were ill for 5 days and longer and fulfilled the inclusion criteria for illness due to infection. The incidence of symptoms of URTI/1000 hours of training for the group of 29 runners was 1,26. The incidence of symptoms for the 10 athletes not fulfilling the inclusion criteria for illness was 0.58 and the incidence for the 12 athletes fulfilling the inclusion criteria was 0.69. The odds ratio for the athletes (n=22) for developing symptoms of URTI during a year is 1.03 compared to the odds ratio of 2.5 for the general population during the similar period. These results seem to indicate that 45% of athletes (n=10) who reported URTI symptoms directly following strenuous exercise do not have clinical infection. Furthermore, the study indicates that regular, moderate, endurance exercise may afford protection against URTI, when compared to the general population. In the second study, 5 athletes (n=5) of the original 12 subjects with URTI complied with all the test protocols. On recruitment, baseline tests were done for muscle strength, muscle endurance, aerobic endurance and maximal effort to exhaustion. Following the development of the URTI, the above parameters were tested over six days on days 0, 2, 4 and 6. After regaining their pre-illness fitness levels over a three-month period, the subjects were detrained for comparative periods and the above tests repeated on similar days for comparative purposes. iv Parameters for muscle strength and muscle endurance [Work (Joule), Power (Watt), Torque to mass (Nm/kg), and Total power (Watt)] appeared to be unaffected following periods of illness and following comparative periods of detraining.